Electricity Potential by Bioethanol Fuel from Pineapple Skin Waste, Kualu Nanas Village, Kampar Regency, Riau - Bijaksana, Varkhan; Miefthawati, Nanda Putri (PROtek : Jurnal Ilmiah Teknik Elektro, 2023)
Kualu Nenas was a pineapple producer in Riau who produced 4 tons of pineapples a day. This production produced 36 tons of waste per month. This waste created problems for the environment, including odor and methane gas, whereas pineapple peel waste included glucose, which can be used to produce bioethanol. This study aimed to analyze the bioethanol potential of pineapple peel and the potential for electricity and power, calculate the values of TFC and SFC, and determine the efficiency of the fuel mixture, which was tested on an 8 kW generator in 30 minutes. This research uses fermentation and distillation methods, which are simulated by a superpro designer. From the research conducted, the potential for bioethanol was 6,262.63 L/month or 68,871.54 L/year with an ethanol content of 99.9995% and 0.0005% water. The electricity is 75.39 MWh/month for E0, 71.98 MWh/month for E10, and 46.88 MWh/month for E100. The power potential generated is 3.14 MW/month for E0, 2.99 MW/month for E10, and 1.95 MW/month for E100. From testing with an 8 kW generator, the TFCs of E0, E10, and E100 fuels were 0.834, 0.835, and 0.839 liters/hour, respectively. While the SFC of E0, E10, and E100 fuels were 0.1043, 0.1044, and 0.1049 liters/hour, with efficiencies of 50.82%, 52.98%, and 80.95%.